Prophetic Transformational Leadership in Islamic Education: Building Human Resource Development in the 21st Century - Moh. Affan (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2025)
Leadership in Islamic education must unite moral values with modern management. The 21st century demands leaders who are competent, ethical, and spiritually grounded. Prophetic transformational leadership, based on the Prophet’s example, emphasizes uswah hasanah, amanah, tabligh, and fathanah. These dimensions strengthen human resource development by fostering competence, motivation, and commitment. This study uses a quantitative approach to test the influence of prophetic leadership on HRD. The results are expected to enrich theory and offer practical guidance for advancing Islamic education today. Recommendation: Keep this version for abstracts or journal submissionsrequiring brevity. Next step: Integrate with keywords and problem statement for coherence.